Acoustic rehabilitation of a music classroom - Paloma Pérez Castillo (Universidad de La Rioja, 2013)
Generallly, music in classrooms lacks apropiate acoustic characteristics. With the help of an análisis of perceptive variables and plysical parameters, those acoustic values which guarantee the acoustic confort have been able identify. These values taken like a criteria to the acoustic restoration of a music classroom sutied before, the reached improvement results satisfactory. With all ol them it pretends to contribute to a better effectiveness of the oral and musical communication for a good development of the music didactics.